Prediction of Epileptic Seizure onset based on EEG signals and learning approaches - Nazim, Tausif; Abid, MD. Bakhtiar; Mamun, Jahid Hasan (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2020.